Coexistence of Myelolipoma and Primary Bilateral Macronodular Adrenal Hyperplasia With GIP-Dependent Cushing's Syndrome - Larose, Stéphanie; Bondaz, Louis; Mermejo, Livia M.; Latour, Mathieu; Prosmanne, Odile; Bourdeau, Isabelle; Lacroix, André (Frontiers in Endocrinology, 2019)
Introduction: Adrenal myelolipomas are usually isolated benign adrenal lesions, but can be found adjacent to steroid-secreting adrenocortical tumors. We studied the aberrant regulation of cortisol secretion in a 61 year-old woman with combined bilateral myelolipomas and primary bilateral macronodular adrenal hyperplasia (BMAH) causing Cushing’s syndrome. The goal was to identify potential aberrant ligands and hormone receptors regulating cortisol excess, using both an in vivo investigation protocol and in vitro studies on resected adrenals. Materials and methods: Cortisol response was measured during in vivo tests that transiently modulated the levels of ligands for potential aberrant receptors, including GIP. Response to medical therapies decreasing GIP was monitored. Expression of ACTH and of GIP receptors were examined in resected adrenal tissues by immunohistochemistry and reverse transcription polymerase chain reaction (RT-PCR). Results: In vivo, cortisol increased in response to mixed meals (+353%), oral 75 g glucose (+71%), GIP infusion (+416%) and hLH IV (+243%). Suppression of GIP by pasireotide improved cortisol secretion but produced hyperglycemia. The left adrenal was predominantly composed of myelolipoma and strands of BMAH, while the right was mainly composed of BMAH with some foci of myelolipoma on pathology. No ACTH was detectable by immunohistochemistry in BMAH or myelolipomas tissue. Ectopic GIP receptor was confirmed by RT-PCR and immunohistochemistry in BMAH tissues but not in the myelolipomas. Conclusion: This is the first report of interspersed myelolipoma and BMAH with GIP-dependent Cushing’s syndrome. Their simultaneous occurrence may suggest yet to be identified adrenocortical tissue paracrine factors regulated by aberrant receptors which could stimulate adipocyte and hematopoietic cell proliferation.